A PepFect14 analog improves non‐viral CRISPR delivery in primary human cells to facilitate genome editing and repair - Alex du Rand; Courtney Masterson; Daniel Verdon; Andrew Siow; Evert Loef; Rod Dunbar; Richard Kingston; Paul Harris; Hilary Sheppard (Bioengineering & Translational Medicine, 2026)
Abstract CRISPR‐based designer nucleases can facilitate genome engineering targeting almost any genomic locus. However, safe and efficient methods for delivering gene editors into primary human cells and tissues remain a central challenge. In this study, we employed a PepFect14 (PF14) analog, PF14‐K, to deliver high‐fidelity Cas9‐ribonucleoproteins and non‐viral repair templates into primary human skin cells to mediate gene editing and repair targeting genes underlying the group of genetic skin blistering disorders epidermolysis bullosa (EB). Peptide‐RNP nanoparticles enabled consistent gene editing of >70% in primary wild type fibroblasts and >50% in primary wild type keratinocytes. In more difficult‐to‐transfect primary EB skin cells, this strategy facilitated up to 68% exon deletion‐mediated reframing targeting COL7A1 and 37% precise homology‐directed repair of a prevalent LAMB3 mutation. Compared to electroporation, the gold standard for ex vivo delivery, PF14‐K enabled similar total yields of edited cells. Deliverable PF14‐K nanoparticles are highly cost‐effective, as they can be formed on the benchtop through a simple mix‐and‐incubate approach, with future potential to deliver base and prime editors.